MY SAY: Stop the nuclear roulette - Razak, Dzulkifli Abd (2011)
At the time of writing, radiation levels in the seawater near the nuclear reactors at Fukushima Daiichi, shattered by the earthquake and tsunami, were said to be rapidly rising. Tests conducted showed that the radioactive iodine level was 3,355 times higher than in the "normal" sea-water around the plant. Not only is the relatively fast-decaying io-dine-131 level up, but more worryingly, so is caesium-137. The latter has a half-life of about 30.17 years compared with only eight days for the former. Meantime, the contamination of nearby farm produce and dairy products has led to an import scare in several countries and the evacuation zone around the plant has been widened to 30km.